A Single Crossing-Over Event in Voltage-Sensitive Na+ Channel Genes May Cause Critical Failure of Dengue Mosquito Control by Insecticides - Hirata, Koichi; Komagata, Osamu; Itokawa, Kentaro; Yamamoto, Atsushi; Tomita, Takashi; Kasai, Shinji (PLoS neglected tropical diseases, 2014)
The voltage-sensitive sodium (Na+) channel (Vssc) is the target site of pyrethroid insecticides. Pest insects develop resistance to this class of insecticide by acquisition of one or multiple amino acid substitution(s) in this channel. In Southeast Asia, two major Vssc types confer pyrethroid resistance in the dengue mosquito vector Aedes aegypti, namely, S989P+V1016G and F1534C. We expressed several types of Vssc in Xenopus oocytes and examined the effect of amino acid substitutions in Vssc on pyrethroid susceptibilities. S989P+V1016G and F1534C haplotypes reduced the channel sensitivity to permethrin by 100- and 25-fold, respectively, while S989P+V1016G+F1534C triple mutations reduced the channel sensitivity to permethrin by 1100-fold. S989P+V1016G and F1534C haplotypes reduced the channel sensitivity to deltamethrin by 10- and 1-fold (no reduction), respectively, but S989P+V1016G+F1534C triple mutations reduced the channel sensitivity to deltamethrin by 90-fold. These results imply that pyrethroid insecticides are highly likely to lose their effectiveness against A. aegypti if such a Vssc haplotype emerges as the result of a single crossing-over event; thus, this may cause failure to control this key mosquito vector. Here, we strongly emphasize the importance of monitoring the occurrence of triple mutations in Vssc in the field population of A. aegypti.